Relations between the motor abilities and the wrestler`s competitive effectiveness - Kostovski, V.; Georgiev, G.; Shala, S.; Ibri, L. (Acta Kinesiologica, 2011)
There was applied a battery of tests using a total number of 22 variables, on a sample of 103 wrestlers. The battery of tests had 17 tests for motor skills` assessing and 5 tests for assessing the wrestler`s competitive effectiveness. The study was done aiming to determine the basic mutual relations. By the analysis of results obtained using the canonical correlation analysis, was showed that the canonical factors could be interpreted as an integral general motor factor, while based on the structure of the wrestler competitive efficiency; the canonical factor can be interpreted as a factor for competitive success. These relations of the canonical factors` structure suggest that wrestlers with these motor abilities achieve very good results in competitions, which fully confirmed the hypothesis of a positive link between these two areas. Based on these obtained research results, can be concluded that for good results and successful competitive efficiency in the wrestling, are necessary quality motor skills.